Polishing pad and polishing method for semiconductor wafer
The use of a resin-based polishing pad with optimized elemental ratios and a strong oxidizing agent solution addresses the instability in conventional semiconductor wafer polishing, achieving improved polishing rates and reduced environmental impact.
Patent Information
- Application Number
- JP2023034103
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-03-06
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-03-06
AI Technical Summary
Conventional polishing methods for semiconductor wafers, particularly difficult-to-polish materials like SiC, GaN, and InP, face challenges in achieving stable polishing rates due to variations in resin composition and the presence of abrasive grains, which can lead to scratches and inhomogeneous polishing.
A resin-based polishing pad and method using a strong oxidizing agent aqueous solution without abrasive grains, where the resin composition is optimized with specific ratios of carbon, hydrogen, oxygen, nitrogen, sulfur, and fluorine to enhance polishing rates, and the use of polymers like PSU, PPSU, PEG#400 acrylic, PC, and PVDF + HFP resins further improves polishing efficiency.
The proposed solution significantly reduces scratch occurrence, achieves stable polishing of semiconductor wafers, and reduces abrasive grain consumption, while also minimizing environmental impact by optimizing the resin composition and using a fine opening filter in the polishing process.
Smart Images

Figure 0007657251000001 
Figure 0007657251000002 
Figure 0007657251000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polishing pad and a polishing method for semiconductor wafers, particularly for wafers that are difficult to polish, such as SiC, GaN, and InP. [Background technology]
[0002] Semiconductor wafers such as SiC wafers, GaN wafers, Si wafers, and Si oxide wafers are known as wafers that are difficult to polish. Conventionally, when polishing such semiconductor wafers, polishing is performed on a polishing plate using a resin polishing pad with abrasive grains fixed thereto. For example, the CMP (Chemical Mechanical Polishing) method described in Patent Document 1 is one such method. In polishing using such abrasive grains, the polishing slurry is usually passed through a foreign matter removal filter during circulation to remove foreign matter from the polishing slurry, and the polishing slurry after the foreign matter removal is supplied to the polishing plate again.
[0003] In the above-mentioned conventional polishing method, if a very fine mesh filter is used to remove the abrasive grains from the polishing slurry, it will be clogged and cannot be used, and if a slightly larger mesh filter is used instead, the filter's removal capacity is insufficient, and the abrasive grains remaining in the polishing slurry may cause scratches on the polished surface of semiconductor wafer.In addition, the specific gravity of the abrasive grains in the polishing slurry is greater than that of the dispersion liquid, and they are likely to settle and aggregate in the storage tank or the conveying pipe line, so when the aggregated abrasive grains flow onto the polishing pad, the abrasive grains are likely to be non-uniformly dispersed on the polishing pad, and non-uniform polishing may occur on the polished surface of wafer.
[0004] In response to this, a polishing method using a resin polishing pad and a chemical liquid has been proposed, for example the polishing method described in Patent Document 2. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special issue number 2013-214784 [Patent Document 2] Patent Publication No. 2021-057368 Summary of the Invention [Problem to be solved by the invention]
[0006] However, since the polishing rate varies depending on the type of resin constituting the polishing pad, stable polishing is not necessarily achieved, and there is a problem that the method is not practical.
[0007] The present invention has been made against the background of the above circumstances, and its object is to provide a polishing pad and polishing method for semiconductor wafers that can stably polish semiconductor wafers using a resin polishing pad and a chemical liquid.
[0008] In light of the above circumstances, the present inventors have conducted various studies on what kind of resin components are effective in improving the polishing rate of semiconductor wafers. First, a resin composed of any one of carbon, hydrogen, oxygen, nitrogen, sulfur, and fluorine was used as a resin plate (polishing table), and a polishing test was carried out on a wafer that is difficult to polish, such as SiC or GaN, while supplying potassium permanganate (KMnO4) liquid as a strong oxidizing agent, and the contribution of each element to the polishing rate was analyzed by regression analysis. As a result, it was found that oxygen, carbon, and fluorine tend to improve the polishing rate, and that nitrogen, sulfur, and hydrogen tend to decrease the polishing rate. From the above facts, it was found that a high polishing rate can be obtained by using a resin with a composition ratio of carbon, hydrogen, oxygen, nitrogen, sulfur, and fluorine such that the polishing rate contribution expressed by the formula (1) satisfies the formula (2) below, and the total of the contents of each element multiplied by the coefficient of regression analysis is the polishing rate contribution frequency (formula (1) described below). The inventors have also found that the polishing rate can be further improved by using an abrasive grain-containing polishing pad made of this resin. The present invention has been made based on this finding. [Means for solving the problem]
[0009] That is, the gist of the semiconductor wafer polishing pad of the first invention is a resin polishing pad for polishing semiconductor wafers using a polishing liquid that is a strong oxidizing agent aqueous solution that does not contain abrasive grains, and the polishing pad is a polymer containing carbon C and at least one of hydrogen H, oxygen O, nitrogen N, sulfur S, and fluorine F, and the content of the hydrogen is M H (weight percentage), the carbon content is M C (weight percentage), the oxygen content is M O (weight percentage), the nitrogen content is M N (weight percentage), the sulfur content is M S (weight percentage), the fluorine content is M F When the polishing rate is expressed as a percentage by weight, the polishing rate contribution frequency PRN is expressed by the formula (1), and the polishing rate contribution frequency PRN satisfies the formula (2). The resin constituting the polishing pad is PSU (polysulfone) resin, PPSU (polyphenylsulfone) resin, PEG#400 acrylic resin (acrylic resin obtained by ultraviolet curing an acrylate monomer in which an acrylic group is bonded to both ends of a polyethylene glycol having an average molecular weight of 400), PC (polycarbonate) resin, PVDF80%+HFP20% (copolymer resin of 80% polyvinylidene fluoride and 20% propylene hexafluoride) resin, )of The point is that it is one of the resins. PRN=-5738M H +849.6M C +1766M O -40.7M N -394.9M S +219.4M F ... (1) 268.4≦PRN≦1516.3 (2)
[0010] The gist of the second invention is a method for polishing a semiconductor wafer, which comprises polishing a semiconductor wafer using a polishing liquid that is an aqueous solution of a strong oxidizing agent that does not contain abrasive grains, and a polishing pad made of resin, the polishing pad being made of a polymer containing carbon and at least one of hydrogen, oxygen, nitrogen, sulfur, and fluorine, and the content of the hydrogen atoms is set to M H (weight percentage), the content of the carbon atoms is M C (weight percentage), the content of the oxygen atoms is M O (weight percentage), the content of the nitrogen atoms is M N (weight percentage), the sulfur content is M S (weight percentage), the content of the fluorine atoms is M F When the polishing rate is expressed as a percentage by weight, the polishing rate contribution frequency PRN is expressed by the above formula (1), and the polishing rate contribution frequency PRN satisfies the above formula (2). The resin constituting the polishing pad is PSU (polysulfone) resin, PPSU (polyphenylsulfone) resin, PEG#400 acrylic resin (acrylic resin obtained by UV-curing an acrylate monomer in which an acrylic group is bonded to both ends of a polyethylene glycol having an average molecular weight of 400), PC (polycarbonate) resin, PVDF80%+HFP20% (copolymer resin of 80% polyvinylidene fluoride and 20% propylene hexafluoride) resin, )of The point is that it is one of the resins. Effect of the Invention
[0011] According to the first invention of the polishing pad for semiconductor wafers and the second invention of the polishing method for semiconductor wafers, a polishing liquid that is an aqueous solution of a strong oxidizing agent that does not contain abrasive grains is used, so that a fine-mesh filter can be used in the middle of the circulation path for circulating the polishing liquid, and therefore the occurrence of scratches can be significantly reduced, stable polishing of semiconductor wafers can be obtained, and the consumption of abrasive grains is suppressed, reducing the environmental load. The resin polishing pad is a polymer containing carbon and at least one of hydrogen, oxygen, nitrogen, sulfur, and fluorine, and the resin constituting the polishing pad is PSU (polysulfone) resin, PPSU (polyphenylsulfone) resin, PEG#400-based acrylic resin (acrylic resin obtained by ultraviolet curing an acrylate monomer in which an acrylic group is bonded to both ends of polyethylene glycol with an average molecular weight of 400), PC (polycarbonate) resin, PVDF80%+HFP20% (copolymer resin of 80% polyvinylidene fluoride and 20% propylene hexafluoride) )of Since the resin is any one of these resins and the polishing rate contribution number PRN of the polishing pad is 268.4 or more and 1516.3 or less, the polishing rate is significantly improved.
[0012] Preferably, the polishing rate contribution number PRN of the polishing pad satisfies the formula (3). According to this, since the polishing rate contribution number PRN of the polishing pad is 268.4 or more and 959.3 or less, the polishing rate is further improved. 268.4≦PRN≦959.3 (3)
[0013] Preferably, the polishing liquid contains an aqueous solution of potassium permanganate as the aqueous solution of the strong oxidizing agent, whereby reduction of potassium permanganate ions contained in the aqueous solution of potassium permanganate is suppressed by the polymer constituting the polishing pad, causing permanganate to precipitate on the polishing pad, and the precipitated particles of permanganate are used as abrasive particles to polish the semiconductor wafer.
[0015] Preferably, the polishing pad does not have abrasive grains and independent or interconnected pores, but may have abrasive grains or independent and / or interconnected pores. More preferably, the polishing pad contains at least one of silica abrasive grains, alumina abrasive grains, zirconia abrasive grains, manganese oxide abrasive grains, and ceria abrasive grains as abrasive grains in the independent and / or interconnected pores. This facilitates planarization polishing due to the ubiquitous distribution of abrasive grains, and increases the number of action points to obtain a high polishing rate.
[0016] In addition, preferably, the gist of the polishing method using the polishing pad is a method for polishing a semiconductor wafer by using a polishing liquid that is a strong oxidizing agent aqueous solution that does not contain abrasive grains, and a polishing pad made of resin, the polishing pad being a polymer containing carbon and at least one of hydrogen, oxygen, nitrogen, sulfur, and fluorine, and the content of the hydrogen atoms is M H ( Weight percentage ), the content of the carbon atoms is M C ( Weight percentage ), the content of the oxygen atoms is M O ( Weight percentage ), the content of the nitrogen atoms is M N ( Weight percentage ), the sulfur content is M S ( Weight percentage ), the content of the fluorine atoms is M F ( Weight percentage ), the polishing rate contribution number PRN is expressed by the formula (1), and the polishing rate contribution number PRN satisfies the formula (2).
[0017] As a result, since the polishing liquid is an aqueous solution of a strong oxidizing agent that does not contain abrasive grains, a fine-mesh filter can be used in the middle of the circulation path for circulating the polishing liquid, so that the occurrence of scratches can be significantly reduced and stable polishing of semiconductor wafers can be obtained, and the consumption of abrasive grains is suppressed, reducing the environmental load. Also, the resin polishing pad is a polymer containing carbon and at least one of hydrogen, oxygen, nitrogen, sulfur, and fluorine, and the polishing rate contribution frequency PRN of the polishing pad is 268.4 or more and 1516.3 or less, so that the polishing rate is significantly improved. [Brief description of the drawings]
[0018] [Figure 1] 1 is a perspective view showing a polishing apparatus for use in polishing by a CMP method, in which a polishing plate according to an embodiment of the present invention is used; [Diagram 2] 2 is a plan view for explaining a rotation mechanism of an application disk of the polishing apparatus of FIG. 1. FIG. [Diagram 3] FIG. 2 is a diagram showing the chemical structure of a PES resin (polyethersulfone resin), which is an example of a resin constituting the polishing pad of FIG. [Figure 4] FIG. 2 is a diagram showing the chemical structure of a PSU resin (polysulfone resin), which is an example of a resin constituting the polishing pad of FIG. [Diagram 5] FIG. 2 is a diagram showing the chemical structure of a PPSU resin (polyphenylsulfone resin), which is an example of a resin constituting the polishing pad of FIG. 1. [Figure 6] FIG. 2 is a diagram showing the chemical structure of a PEEK resin (polyether ether ketone resin), which is an example of a resin constituting the polishing pad of FIG. [Figure 7] FIG. 2 is a diagram showing the chemical structure of a PU resin (polyurethane resin synthesized from isocyanate and polyol), which is an example of a resin constituting the polishing pad of FIG. 1. [Figure 8] FIG. 2 is a diagram showing the chemical structure of a PET resin (polyethylene terephthalate (polyester) resin), which is an example of a resin constituting the polishing pad of FIG. 1. [Figure 9]FIG. 2 is a diagram showing the chemical structure of an EP resin (cured epoxy resin), which is an example of a resin constituting the polishing pad of FIG. 1. [Figure 10] FIG. 2 is a diagram showing the chemical structure of a PEG#400 acrylic resin, which is an example of a resin constituting the polishing pad of FIG. 1. [Figure 11] Fig. 2 is a diagram showing the chemical structural formula of PC resin (polycarbonate resin), which is an example of the resin constituting the polishing pad of Fig. 1. Fig. 3 is a schematic diagram showing the network structure of an epoxy resin. [Figure 12] FIG. 2 is a diagram showing the chemical structure of a copolymer resin of 80% polyvinylidene fluoride and 20% hexafluoropropylene (PVDF(80%)-HFP(20%) resin), which is an example of the resin constituting the polishing pad of FIG. 1. [Figure 13] FIG. 2 is a diagram showing the chemical structure of PVDF (polyvinylidene fluoride resin), which is an example of a resin constituting the polishing pad of FIG. [Figure 14] FIG. 2 is a diagram showing the chemical structure of a melamine resin (thermosetting product) which is a comparative example resin constituting the polishing pad of FIG. 1. [Figure 15] FIG. 2 is a diagram showing the chemical structure of PA6 (polyamide 6 resin), which is a comparative resin constituting the polishing pad of FIG. [Figure 16] FIG. 2 is a diagram showing the chemical structure of a PPS resin (linear polyphenylene sulfide resin) which is a comparative resin constituting the polishing pad of FIG. 1. [Figure 17] 1 is a table showing the resin of the polishing pad used in polishing SiC in Experimental Example 1, the regression analysis coefficient for each element constituting the resin, the polishing rate, the surface roughness, and the polishing rate contribution frequency. [Figure 18] FIG. 13 is a diagram showing the polishing rate contribution frequency of the resin of the polishing pad used in each polishing example of Experimental Example 1 and the actual polishing rate. [Figure 19] FIG. 1 is a diagram showing a polymer structure containing only carbon C and oxygen O, with the oxygen O being more abundant, which is theoretically considered to be capable of achieving the highest polishing rate contribution number PRN. [Figure 20]FIG. 2 is a diagram showing a paste-like precipitated substance adhering to the polishing surface of a polishing pad, using an SEM photograph taken with a scanning electron microscope. [Figure 21] FIG. 21 is a diagram showing a comparison between an X-ray diffraction pattern obtained by performing X-ray diffraction on the particulate matter shown in the SEM photograph of FIG. 20 and an X-ray diffraction pattern of potassium permanganate. [Figure 22] 1 is a table showing the resin, polishing rate, and surface roughness of the polishing pad used in polishing SiC in Experimental Example 2. [Figure 23] 5 is a schematic diagram illustrating the structure of an abrasive-containing polishing pad among the polishing pads of Example 2. FIG. [Figure 24] FIG. 2 is a schematic diagram illustrating the polishing mechanism of an abrasive-containing polishing pad LHA (registered trademark). [Diagram 25] 1 is a table showing the resin, polishing rate, and surface roughness of the polishing pad used in polishing SiC in Experimental Example 3. [Figure 26] 1 is a table showing the resin, polishing rate, and surface roughness of the polishing pad used in polishing SiC in Experimental Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] An embodiment of the present invention will now be described with reference to the drawings. Note that in the following embodiment, the drawings are appropriately simplified or modified, and the dimensional ratios and shapes of the various parts are not necessarily drawn accurately. EXAMPLES
[0020] Fig. 1 conceptually shows the main part of a surface polishing apparatus 10 for polishing compound semiconductor wafers such as SiC wafers, GaN wafers, and InP wafers, as an example of the present invention, with the guide roller fixing table removed. In Fig. 1, the surface polishing apparatus 10 is provided with a circular polishing platen (rotary table) 12 supported so as to be rotatable about its vertical rotation axis C1, and the polishing platen 12 is rotated at a constant speed in one rotation direction indicated by the arrow in the figure by a platen driving motor 14. A sheet-shaped resin polishing pad 18 is attached to the upper surface of the polishing platen 12, i.e., the surface against which a workpiece (semiconductor wafer) 16 is pressed.
[0021] The workpiece 16 is held on the lower surface of the application disc 20, i.e., the surface facing the polishing pad 18, and the application disc 20 presses the workpiece 16 against the polishing pad 18 with a predetermined load. A drip nozzle 22 is provided near the application disc 20 of the surface polishing device 10, and a polishing liquid (lubricant) PF delivered from a tank (not shown) is supplied onto the polishing surface plate 12.
[0022] The surface polishing apparatus 10 is provided, as required, with an adjustment tool holding member (not shown) that is arranged to be rotatable about a rotation axis parallel to the rotation axis C1 of the polishing table 12 and to be movable in the direction of the rotation axis and in the radial direction of the polishing table 12, and an abrasive body adjustment tool (dresser or conditioner) such as a diamond wheel (not shown) that is attached to the lower surface of the adjustment tool holding member, i.e., the surface facing the polishing pad 18. The adjustment tool holding member and the abrasive body adjustment tool attached thereto are pressed against the polishing pad 18 while being rotated and driven by an adjustment tool driving motor (not shown), and are moved back and forth in the radial direction of the polishing table 12, thereby adjusting the polishing surface of the polishing pad 18 and constantly maintaining the surface state of the polishing pad 18 in a state suitable for polishing.
[0023] 2, at a position eccentric from the rotation axis C1 on the polishing table 12, the outer peripheral surface of a short cylindrical attachment disk 20, which holds the workpiece 16 to be polished on its underside by suction, adhesion, or a holding frame, is received by a pair of free-rotating guide rollers 30 and a drive guide roller 32 provided on a guide roller fixing base 28, which is fixed in a position fixed to a frame (not shown), so that the attachment disk 20 can rotate about the rotation axis C2. The attachment disk 20 is rotated about the rotation axis 2 by the rotation force based on the difference in peripheral speed of the polishing table or polishing pad 18, while the attachment disk 20 is pressed against the polishing pad 18 on the polishing table 12 by the load of, for example, a weight 34, thereby polishing the workpiece 16.
[0024] The following polishing method is applied during polishing by the polishing apparatus 10. That is, while the polishing pad 18 attached to the polishing table 12, the attachment disk 20, and the workpiece 16 held on its lower surface are rotated about their respective rotation axes C1 and C2 by the table drive motor 14 and the drive guide roller 32, the polishing liquid PF not containing abrasive grains is supplied from the drip nozzle 22 onto the surface of the polishing pad 18, while the workpiece 16 held on the attachment disk 20 is pressed against the polishing pad 18. As a result, the surface to be polished of the workpiece 16, i.e., the surface facing the polishing pad 18, is polished flat by the chemical polishing action of the polishing liquid PF.
[0025] The polishing pad 18 is formed into a sheet from a dense resin that does not contain bubbles or abrasive grains, a porous resin that contains independent or interconnected pores, or an abrasive grain-containing resin that contains abrasive grains (silica) in the independent or interconnected pores. These resins are polymers that contain carbon C and at least one of hydrogen H, oxygen O, nitrogen N, sulfur S, and fluorine F, and the hydrogen H content is M H ( Weight percentage ), the carbon C content is M C ( Weight percentage ), and the oxygen O content is M O ( Weight percentage ), the nitrogen N content is M N ( Weight percentage ), the sulfur S content is M S ( Weight percentage ), the fluorine F content is M F ( Weight percentage ), the resin has a polishing rate contribution frequency PRN expressed by the formula (1), and the polishing rate contribution frequency PRN satisfies the formula (2), and preferably the resin satisfies the formula (3). PRN=-5738M H +849.6M C +1766M O -40.7M N -394.9M S +219.4M F ... (1) 268.4≦PRN≦1516.3 (2) 268.4≦PRN≦959.3 (3)
[0026] Resins whose polishing rate contribution frequency PRN satisfies formula (3) include PES resin (polyethersulfone resin) represented by the chemical structural formula in Figure 3, PSU resin (polysulfone resin) represented by the chemical structural formula in Figure 4, PPSU resin (polyphenylsulfone resin) represented by the chemical structural formula in Figure 5, PEEK resin (polyether ether ketone resin) represented by the chemical structural formula in Figure 6, PU resin (polyurethane resin synthesized from isocyanate and polyol) represented by the chemical structural formula in Figure 7, PET resin (polyethylene terephthalate (polyester) resin) represented by the chemical structural formula in Figure 8, and EP resin (cured epoxy resin) represented by the chemical structural formula in Figure 9. 10, a copolymer resin of 80% polyvinylidene fluoride and 20% hexafluoropropylene (PVDF(80%)-HFP(20%) resin) represented by the chemical structural formula in FIG. 12, and PVDF(100%) resin (polyvinylidene fluoride resin) represented by the chemical structural formula in FIG. 13.
[0027] [Experimental Example 1] Hereinafter, an experimental example of polishing a semiconductor wafer conducted by the present inventors will be described. First, using an apparatus configured similarly to the polishing apparatus 10 shown in FIG. 1, 14 types of polishing processes using Comparative Example 1-3, which is a polishing pad made of a resin whose chemical structure is shown in FIG. 14-FIG. 16, and Example 1-11, which is a polishing pad made of a resin whose chemical structure is shown in FIG. 4-FIG. 13, were performed on a 4-inch φ SiC wafer under the following polishing test conditions 1. The resin of Comparative Example 1-3 and Example 1-11 is a resin plate that does not contain abrasive grains and pores. The polishing rate PR and surface roughness Sa of the SiC wafer after the polishing test were measured using the following polishing rate measurement method and surface roughness measurement method. In addition, the polishing rate contribution frequency PRN was calculated using the formula (1) for each of the polishing pads used in Comparative Example 1-3 and Example 1-11.
[0028] [Polishing test condition 1] Workpiece: 4-inch diameter SiC wafer (0001) surface, tilt angle 4° Workpiece rotation speed: 60 rpm Polishing pad diameter: 300mmφ Polishing pad rotation speed: 60 rpm Polishing pressure: 42kPa Polishing liquid: KMnO4 (0.25mol / l) pH=3.2 Polishing liquid flow rate: 10ml / min
[0029] [Method of measuring polishing rate] The difference in mass of the workpiece before and after the polishing test was determined using an analytical balance, and the amount of polishing (wear thickness) was calculated from the known density of the workpiece and the surface area of the polished surface. The polishing rate PR (nm / h) was calculated by dividing the amount of polishing by the polishing time.
[0030] [Surface roughness measurement method] The surface roughness of the surface profile of the polished surface of the silicon wafer after the polishing test was measured using a white light interference microscope (Hitachi High-Tech VS-1330), and the arithmetic mean roughness Sa specified in ISO25178 was calculated.
[0031] FIG. 17 shows the types of resins constituting the three types of polishing pads used in Comparative Examples 1-3 and the eleven types of polishing pads used in Examples 1-11, obtained in Experimental Example 1, and the contents ( Weight percentage ), the polishing test results (polishing rate PR (nm / h) and surface roughness Sa (nm) of the polished surface), and the polishing rate contribution number PRN are shown.
[0032] In Fig. 17, the polishing pads of Comparative Examples 1 to 3 are a group of polishing pads with relatively poor practicality, with the polishing rate PR being below the practicality criterion value of 249 (nm / min), while the polishing pads used in Examples 1 to 11 are a group of polishing pads that are practically acceptable, with the polishing rate PR being above the practicality criterion value of 250 (nm / min). There is not much difference in the average surface roughness Sa (nm) between the polishing pads of Comparative Examples 1 to 3 and Examples 1 to 11. The practicality criterion value of the polishing rate PR is set to three times the polishing rate PR of the polishing pad made of melamine resin.
[0033] (Derivation of formula (1) for polishing rate contribution number PRN) In FIG. 17, the polishing rate PR of the PET resin of Example 6 is increased by about two times compared to the PU resin of Example 5, because the bond between nitrogen (N) and hydrogen (H) is replaced by a bond between carbon (C) and oxygen (O). The polishing rate PR of the PPS resin of Comparative Example 3 is reduced to about 1 / 4 compared to the PES resin of Example 1, because oxygen (O) is eliminated. The polishing rate PR of the PEEK resin of Example 4 is increased by about 1.2 times compared to the PES resin of Example 1, because sulfur (S) is eliminated. The polishing rate PR of the PEG#400 acrylic resin of Example 8 is increased by about 1.2 times compared to the PES resin of Example 1, because sulfur (S) is eliminated. From these facts, it is presumed that carbon (C) and oxygen (O) atoms have the effect of increasing the polishing rate PR, and sulfur (S), nitrogen (N), and hydrogen (H) atoms have the effect of increasing the polishing rate PR.
[0034] The coefficients of the regression analysis (relative to content) in FIG. 17 are the coefficients of the regression equation obtained by performing regression analysis on each of carbon C, hydrogen H, oxygen O, nitrogen N, sulfur S, and fluorine F contained in Comparative Examples 1 to 3 and Example 1 to 11. Among these coefficients, H atoms, N atoms, and S atoms, which have negative coefficients, have the effect of lowering the polishing rate PR, while C atoms, O atoms, and F atoms, which have positive coefficients, have the effect of raising the polishing rate PR. It has been made clear that the positive and negative coefficients of the respective coefficients of the C atoms, H atoms, O atoms, N atoms, S atoms, and F atoms correspond to the oxidizing and reducing properties of these atoms. Therefore, the hydrogen content is expressed as M H ( Weight percentage ), the carbon content is M C ( Weight percentage ), the oxygen content is M O ( Weight percentage ), the nitrogen content is M N ( Weight percentage ), the sulfur content is M S ( Weight percentage ), the fluorine content is M F ( Weight percentage ), the coefficient of each element obtained by regression analysis is applied to each content, and the polishing rate contribution number PRN is defined as shown in the above-mentioned formula (1).
[0035] (Derivation of the range of polishing rate contribution number PRN) When the polishing rate contribution number PRN is calculated for each of the comparative examples 1 to 3 and the example products 1 to 11 using formula (1), the values shown in FIG. 17 are obtained. The relationship between the polishing rate contribution number PRN and the polishing rate PR (nm / h) of each of the comparative examples 1 to 3 and the example products 1 to 11 is as shown in FIG. 18. In FIG. 18, the minimum value of the polishing rate contribution number PRN for the example products 1 to 11 is 268 and the maximum value is 959.3. This leads to the above-mentioned formula (3).
[0036] Incidentally, among the coefficient values of carbon C, hydrogen H, oxygen O, nitrogen N, sulfur S, and fluorine F contained in the embodiment product 1-11 of formula (1), the element that contributes most to the polishing rate contribution number PRN is oxygen O. Also, in order to be a resin that constitutes a polishing pad, carbon C is essential as the skeleton of the polymer structure. Therefore, from these facts, it is theoretically considered that a molecular structure that contains only carbon C and oxygen O and has the largest amount of oxygen O can maximize the polishing rate contribution number PRN. Such a resin has a polymer structure shown in FIG. 19. In this polymer, the molar ratio of carbon C to the molar ratio of oxygen O is 1:2 because the atomic weight of carbon C is 12.01 and the atomic weight of oxygen O is 15.99. Also, the mass ratio of carbon C to the mass ratio of oxygen O is 0.273:0.727.
[0037] Thus, the mass ratio of carbon C to oxygen O is 0.273:0.727, so the hydrogen H content M H = 0, carbon C content M C = 0.273, oxygen O content M O = 0.727, Nitrogen N content M N = 0, sulfur S content M S = 0, fluorine F content M F If we substitute 0 into the right side of equation (1), we obtain 1516.3 as the theoretical maximum value of the polishing rate contribution number PRN. This leads to equation (2) above.
[0038] (Explanation of polishing mechanism) Next, the polishing mechanism that enables polishing without using abrasive grains in polishing processing of SiC wafers using Comparative Example 1-3 and Example 1-11, which are made of resin plates that do not contain abrasive grains and pores, as polishing pads, will be described below. First, when the potassium permanganate aqueous solution that constitutes the polishing liquid comes into contact with a resin that is highly oxidizing because it contains C atoms, O atoms, and / or F atoms, it is difficult for it to take electrons from the resin, and the oxidation reaction shown in formulas (4) and (5) is unlikely to occur. Under these circumstances, potassium permanganate KMnO4, which is a fine crystal that functions as an abrasive grain, is precipitated due to moisture evaporation caused by the heat during polishing. At this time, potassium permanganate KMnO4 as the precipitated abrasive grains has high electron stripping ability as shown in formulas (4) and (5), so that the oxidizing ability is high and the polishing rate is high. On the other hand, when the potassium permanganate aqueous solution that constitutes the polishing liquid comes into contact with a resin that is highly reducing because it contains H atoms, N atoms, and S atoms, it is converted into KMnO4 (MnO4 - ion) is reduced to Mn 2+ The dissolution of ions or the precipitation of MnO2 occurs. 2+ When ions are dissolved, there is no solid material to serve as abrasive grains, so polishing is not possible or the polishing rate is very low. Also, when MnO2 is precipitated, the electron stripping ability is low as shown in formula (6), so the oxidizing power is low and the polishing rate is low.
[0039] MnO4 - +8H + +5e - ⇔Mn 2+ +4H2O (4) MnO4 - +4H + +3e - ⇔MnO2+2H2O (5) MnO2+4H + +2e - →Mn 2+ +2H2O (6)
[0040] FIG. 20 shows an SEM photograph of minute precipitates (KMnO4 crystals) CP contained in the paste-like material on the surface of a polishing pad made of a resin having a strong oxidizing power due to the above-mentioned C atoms, O atoms, and / or F atoms, i.e., any of the resins of the examples 1-11, which come into contact with the potassium permanganate aqueous solution constituting the polishing liquid. FIG. 21 shows the X-ray diffraction spectrum of the precipitates CP. In FIG. 21, the X-ray diffraction spectrum of the precipitates CP matches the peak pattern of KMnO4, so it can be seen that the precipitates CP are precipitates of KMnO4. Since the precipitates CP of KMnO4 function as abrasive grains, SiC wafers can be polished even with a polishing pad made of a resin plate that does not contain abrasive grains or pores.
[0041] [Experimental Example 2] Next, the polishing pads of Comparative Example 4-7 and Example 12-18 shown in FIG. 22 were applied to an apparatus configured similarly to the polishing apparatus 10 shown in FIG. 1, and a 4-inch φ SiC wafer was polished under the same polishing test condition 2 as the polishing test condition 1. This Experimental Example 2 differs from Experimental Example 1 in that a commercially available polishing pad or a polishing pad containing abrasive grains is used, that Comparative Example 4 uses a free abrasive grain slurry containing silica abrasive grains, and that Example 13, 15, 17, and 18 are abrasive grain-containing polishing pads. As described above, the resins constituting the polishing pads of Example 12-18 are all resins whose polishing rate contribution frequency PRN satisfies formula (3).
[0042] In Fig. 22, Comparative Example 4 and Comparative Example 7 have in common the point of using a nonwoven fabric pad (polyurethane-impregnated polyester fiber), but the polishing rate PR in the polishing using Comparative Example 4 is more than twice as high as that in the polishing using Comparative Example 7. This is considered to be because a free abrasive slurry is used. Moreover, Example Products 12-18 have a higher polishing rate PR than Comparative Example 5.
[0043] In FIG. 22, Example 12 and Example 13 are common in that they are epoxy resin pads, but Example 13 is different in that it is an abrasive grain-containing resin pad containing silica abrasive grains, and the polishing rate PR is about 1.4 times higher than Example 12. Similarly, Example 14 and Example 15 are common in that they are PEG#400 acrylic resins, but Example 15 is different in that it is an abrasive grain-containing resin pad containing silica abrasive grains, and the polishing rate PR is about 1.8 times higher than Example 14. Also, Example 16 and Example 17 are common in that they are PES resin pads, but Example 17 is different in that it is an abrasive grain-containing resin pad containing silica abrasive grains, and the polishing rate PR is about 2.1 times higher than Example 16. Example 18 is the same abrasive grain-containing resin pad as Example 17, but differs in that the contained abrasive grains are ceria abrasive grains. Example 18, which is an abrasive grain-containing resin pad containing ceria abrasive grains, has a relatively high polishing rate PR of about 0.84 times that of Example 17, which is an abrasive grain-containing resin pad containing silica abrasive grains.
[0044] Fig. 23 is a schematic diagram for explaining the structure of the above-mentioned abrasive grain-containing polishing pad. In Fig. 23, the base resin 42 of the abrasive grain-containing polishing pad LHA is fibrous with an average cross-sectional diameter of, for example, about 0.05 (μm), and abrasive grains 44 with an average particle diameter of, for example, 0.3 (μm) are present in the gaps of the fibrous base resin 42, either partially fixed to the outer periphery of the base resin 42 or separated from the base resin 42 in the gaps. Considering the communication holes 46 that connect the gaps between the fibrous base resin 42, it can be said that the abrasive grains 44 are provided in the communication holes 46. The communication holes 46 are formed to communicate with vertically elongated holes not shown and to communicate with each other. That is, the polishing grains 44 are present in a state where some of them are fixed to the inner walls of the communicating pores 46, or in a state where they are separated from the matrix resin 42 within the communicating pores 46, and each communicating pore 46 is formed in the matrix resin 42 while containing at least one polishing grain 44. During polishing using this abrasive-containing polishing pad LHA, the polishing grains 44 contained in the abrasive-containing polishing pad LHA are supplied to the polishing surface, increasing the polishing rate PR.
[0045] (Explanation of the polishing mechanism of abrasive-containing polishing pads) Fig. 24 is a schematic diagram for explaining the polishing mechanism of the abrasive grain-containing polishing pad LHA. In Fig. 24, the surface and the communicating pores 46 of the abrasive grain-containing polishing pad LHA are filled with the polishing liquid PF by dropping the polishing liquid PF. As a result, the potassium permanganate aqueous solution constituting the polishing liquid PF comes into contact with the base resin 42, which contains C atoms, O atoms, and / or F atoms and has a strong oxidizing power, and electrons are taken away by the oxidation reaction shown in the above formula (4) or (5), and minute precipitates (KMnO4 crystals) CP that function as abrasive grains are precipitated. In this state, when the workpiece 16 is moved on the surface of the abrasive grain-containing polishing pad LHA, the precipitates (KMnO4 crystals) CP and the polishing grains 44 hit the workpiece 16, and the frequency with which the precipitates CP hit the workpiece 16 is increased by the movement of the polishing grains 44, so that a high polishing rate PR is obtained.
[0046] [Experimental Example 3] Next, the polishing pads of Comparative Examples 8-9 and Example Products 19-25 shown in FIG. 25 were applied to an apparatus configured similarly to the polishing apparatus 10 shown in FIG. 1, and a 2-inch φ GaN wafer was polished under the polishing test condition 3. This Experimental Example 3 differs from Experimental Example 1 in that a GaN wafer was polished, that Comparative Example 8 used a free abrasive slurry containing silica abrasive grains, and that Example Products 21, 23, 24, and 25 were abrasive-containing polishing pads. As described above, the resins constituting the polishing pads of Example Products 19-258 are all resins whose polishing rate contribution frequency PRN satisfies formula (3).
[0047] [Polishing test condition 3] Workpiece: 2-inch diameter GaN wafer (0001) Ga surface Workpiece rotation speed: 60 rpm Polishing pad diameter: 300mmφ Polishing pad rotation speed: 60 rpm Polishing pressure: 50kPa Polishing liquid: KMnO4 (0.25mol / l) pH=1.0 Polishing slurry: KMnO4 (0.25 mol / l) pH=1.0 + Silica (12.5wt%) Polishing liquid flow rate: 10ml / min
[0048] In Fig. 25, Comparative Example 8 and Comparative Example 9 have in common the fact that they are both hard polyurethane resin pads (with pores), but the polishing rate PR in polishing using Comparative Example 8 is 10 times higher than that in polishing using Comparative Example 9. This is believed to be because a free abrasive slurry is used. Moreover, Example Products 19-25 have a higher polishing rate PR than Comparative Example 9.
[0049] In FIG. 25, Example 19, Example 20, and Example 21 are common in that they are PES resin pads, but Example 19 is a resin plate without pores, Example 20 is a resin pad with interconnected pores, and Example 21 is an abrasive-containing polishing pad containing silica abrasive grains. Example 21 has a polishing rate PR about 10 times higher than Example 19 and Example 20. Example 22 and Example 23 are common in that they are PEG#400 resin pads, but Example 22 is a resin pad with independent pores, and Example 23 is an abrasive-containing polishing pad containing silica abrasive grains. Example 23 has a polishing rate PR about 6.5 times higher than Example 22. Example 24 differs from Comparative Example 9 in that it is a PVDF (80%) + HFP (20%) resin silica abrasive grain-containing polishing pad, and a polishing rate PR about 33 times higher is obtained. Example 25 differs from Comparative Example 9 in that it is an epoxy resin silica abrasive grain-containing polishing pad, and a polishing rate PR about 30 times higher is obtained.
[0050] [Experimental Example 4] Next, the polishing pads of Comparative Example 10 and Examples 26-27 shown in FIG. 26 were applied to an apparatus configured similarly to the polishing apparatus 10 shown in FIG. 1, and a 2-inch InP wafer was polished under the polishing test condition 4. Experimental Example 4 differs from Experimental Example 1 in that an InP wafer was polished, that a free abrasive slurry containing silica abrasive grains was used in the case of Comparative Example 10, and that Example 27 is an abrasive-containing polishing pad. As described above, the resins constituting the polishing pads of Examples 26-27 are all resins whose polishing rate contribution number PRN satisfies formula (3).
[0051] [Polishing test condition 4] Workpiece: 2-inch diameter InP wafer (100) Workpiece rotation speed: 90 rpm Polishing pad diameter: 300mmφ Polishing pad rotation speed: 90 rpm Polishing pressure: 14kPa Polishing liquid: KMnO4 (0.25mol / l) pH=6.9 Polishing slurry: KMnO4 (0.25 mol / l) pH=6.7 + Silica (12.5wt%) Polishing liquid flow rate: 10ml / min
[0052] In Fig. 26, Comparative Example 10 is a hard polyurethane resin pad (with pores) and uses a free abrasive slurry, so a relatively high polishing rate PR is obtained. Example 26 is made of a PES resin plate that does not contain pores or abrasives, and obtains a polishing rate PR that is about 8% higher than Comparative Example 10. Example 27 is made of an abrasive-containing PES resin pad that has interconnected pores and contains silica abrasives in the interconnected pores, and obtains a polishing rate PR that is about twice as high as Comparative Example 10.
[0053] As described above, according to the polishing pad 18 made of resin and the polishing method using the polishing pad 18 of this embodiment, since the polishing liquid PF, which is an aqueous solution of a strong oxidizing agent that does not contain abrasive grains, is used, a fine-mesh filter can be used in the middle of the circulation path for circulating the polishing liquid PF, so that the occurrence of scratches can be significantly reduced, stable polishing of semiconductor wafers can be obtained, and the consumption of abrasive grains is suppressed, reducing the environmental load. In addition, the resin polishing pad is a polymer containing carbon and at least one of hydrogen, oxygen, nitrogen, sulfur, and fluorine, and the polishing rate contribution frequency PRN of the polishing pad is 268.4 or more and 1516.3 or less, so that the polishing rate is stably and significantly improved.
[0054] In addition, according to the polishing pad 18 made of the resin of this embodiment and the polishing method using the polishing pad 18, preferably, the polishing rate contribution number PRN of the polishing pad satisfies the formula (3). According to this, since the polishing rate contribution number PRN of the polishing pad is 268.4 or more and 959.3 or less, the polishing rate is further improved.
[0055] According to the polishing pad 18 made of resin and the polishing method using the polishing pad 18 of this embodiment, the polishing liquid PF contains an aqueous solution of potassium permanganate as an aqueous solution of a strong oxidizing agent. As a result, the reduction of permanganate ions contained in the aqueous solution of potassium permanganate is suppressed by the polymer constituting the polishing pad 18, causing permanganate to precipitate on the polishing pad 18, and the workpiece (semiconductor wafer) 16 is polished using the precipitated particles CP of permanganate as abrasive particles.
[0056] According to the polishing pad 18 made of the resin of this embodiment and the polishing method using the polishing pad 18, the resin constituting the polishing pad 18 is any one of PES (polyethersulfone) resin, PSU (polysulfone) resin, PEEK (polyetheretherketone) resin, PU (polyurethane) resin, PET (polyethylene terephthalate (polyester)) resin, EP (epoxy) resin cured product (cured product of glycidyl ether type epoxy and amine-based curing agent), PEG#400-based acrylic resin (acrylic resin obtained by ultraviolet curing an acrylate monomer in which an acrylic group is bonded to both ends of polyethylene glycol with an average molecular weight of 400), PC (polycarbonate) resin, PVDF80%+HFP20% (copolymer resin of polyvinylidene fluoride 80% and propylene hexafluoride 20%), and PVDF100% (polyvinylidene fluoride resin). As a result, when the polishing liquid PF containing metal ions comes into contact with the polishing pad 18, metal oxide particles are precipitated on the polishing pad 18.
[0057] In addition, according to the polishing pad 18 made of the resin of this embodiment and the polishing method using the polishing pad 18, the polishing pad 18 may not have abrasive grains and independent or interconnected pores, but may have abrasive grains and independent and / or interconnected pores. More preferably, the polishing pad 18 contains at least one of silica abrasive grains, alumina abrasive grains, zirconia abrasive grains, manganese oxide abrasive grains, and ceria abrasive grains as abrasive grains in the independent and / or interconnected pores. This facilitates planarization polishing due to the ubiquitous distribution of abrasive grains, and increases the number of action points to obtain a high polishing rate.
[0058] According to the polishing method using the polishing pad 18 made of resin of this embodiment, a semiconductor wafer is polished using a polishing solution PF, which is a strong oxidizing agent aqueous solution that does not contain abrasive grains, and a resin polishing pad 18, and the polishing pad is a polymer containing carbon and at least one of hydrogen, oxygen, nitrogen, sulfur, and fluorine, and the content of the hydrogen atoms is M H ( Weight percentage ), the content of the carbon atoms is M C ( Weight percentage ), the content of the oxygen atoms is M O ( Weight percentage ), the content of the nitrogen atoms is M N ( Weight percentage ), the sulfur content is M S ( Weight percentage ), the content of the fluorine atoms is M F ( Weight percentage ), the polishing rate contribution number PRN is expressed by the formula (1), and the polishing rate contribution number PRN satisfies the formula (2).
[0059] As a result, since the polishing liquid PF, which is an aqueous solution of a strong oxidizing agent that does not contain abrasive grains, is used, a fine-mesh filter can be used in the middle of the circulation path for circulating the polishing liquid PF, so that the occurrence of scratches can be significantly reduced, stable polishing of semiconductor wafers can be obtained, and the consumption of abrasive grains 44 is suppressed, reducing the environmental burden. Also, the resin polishing pad 18 is a polymer containing carbon and at least one of hydrogen, oxygen, nitrogen, sulfur, and fluorine, and the polishing rate contribution frequency PRN of the polishing pad is 268.4 or more and 1516.3 or less, so that the polishing rate is significantly improved.
[0060] Although the preferred embodiment of the present invention has been described in detail above with reference to the drawings, the present invention is not limited to this embodiment and may be carried out in other embodiments.
[0061] For example, in the above-described embodiment, the polishing pad 18 is called an LHA pad (registered trademark), and its base resin 42 is fibrous, but this is merely a preferred form of the present invention, and the base resin 42 in the polishing pad 18 of the present invention may be composed of a dense resin that does not have pores or abrasive grains, so long as it is a resin that contains carbon C and at least one of hydrogen H, oxygen O, nitrogen N, sulfur S, and fluorine F in each repeating unit.
[0062] In the above-described embodiment, the polishing pad 18, particularly the LHA pad effective for polishing GaN wafers, has mesh-like communicating pores 46, but it may have bubble-like communicating pores 46 or may be made of a dense resin without communicating pores 46.
[0063] In the above-mentioned embodiment, the polishing liquid PF may contain sodium permanganate ions obtained by dissolving sodium permanganate in water. In this case, when the polishing liquid PF comes into contact with the polishing pad 18, sodium permanganate precipitates on the polishing pad 18 as a permanganate salt.
[0064] Note that the above is merely one embodiment, and other examples are not provided, but the present invention can be implemented in various forms with various modifications and improvements based on the knowledge of those skilled in the art without departing from the spirit of the present invention. [Explanation of symbols]
[0065] 10: Polishing processing equipment 16: Workpiece (semiconductor wafer) 18: Polishing pad 42: Base resin 44: Abrasive grain 46: Stoma PF: Polishing fluid CP: Permanganate precipitate particles (abrasive particles)
Claims
1. A polishing pad for a semiconductor wafer, which polishes a semiconductor wafer using a polishing liquid that is a strong oxidizing agent aqueous solution that does not contain abrasive grains, The polishing pad is made of a polymer containing carbon C and at least one of hydrogen H, oxygen O, nitrogen N, sulfur S, and fluorine F, and the content of the hydrogen is M H (weight percentage), the carbon content is M C (weight percentage), the oxygen content is M O (weight percentage), the nitrogen content is M N (weight percentage), the sulfur content is M S (weight percentage), the fluorine content is M F (weight ratio), the polishing rate contribution number PRN is expressed by the formula (1), and the polishing rate contribution number PRN satisfies the formula (2), The resin constituting the polishing pad is any one of PSU (polysulfone) resin, PPSU (polyphenylsulfone) resin, PEG#400 acrylic resin (acrylic resin obtained by UV-curing an acrylate monomer in which an acrylic group is bonded to both ends of a polyethylene glycol having an average molecular weight of 400), PC (polycarbonate) resin, and PVDF 80% + HFP 20% (copolymer resin of polyvinylidene fluoride 80% and propylene hexafluoride 20%). A polishing pad for semiconductor wafers. PRN=-5738M H +849.6M C +1766M O -40.7M N -394.9M S +219.4M F ・・・ (1) 268.4≦PRN≦1516.3 … (2)
2. The polishing rate contribution number PRN of the polishing pad satisfies the formula (3).
2. The semiconductor wafer polishing pad of claim 1. 268.4≦PRN≦959.3 … (3)
3. The polishing liquid contains an aqueous solution of potassium permanganate as the aqueous solution of the strong oxidizing agent.
2. The semiconductor wafer polishing pad of claim 1.
4. The polishing pad is made of any one of a resin having no abrasive grains and no independent or interconnected pores, a resin having independent and / or interconnected pores, and a resin containing at least one of silica abrasive grains, alumina abrasive grains, zirconia abrasive grains, manganese oxide abrasive grains, and ceria abrasive grains as abrasive grains within the independent and / or interconnected pores.
2. The semiconductor wafer polishing pad of claim 1.
5. A method for polishing a semiconductor wafer, comprising the steps of: polishing the semiconductor wafer using a polishing liquid that is an aqueous solution of a strong oxidizing agent that does not contain abrasive grains; and polishing the semiconductor wafer using a resin polishing pad, the method comprising the steps of: The polishing pad is made of a polymer containing carbon and at least one of hydrogen, oxygen, nitrogen, sulfur, and fluorine, and the content of the hydrogen atoms is M H (weight percentage), the carbon atom content is M C (weight percentage), the content of the oxygen atoms is M O (weight percentage), the content of the nitrogen atoms is M N (weight percentage), the sulfur content is M S (weight percentage), the content of the fluorine atoms is M F (weight ratio), the polishing rate contribution number PRN is expressed by the formula (1), and the polishing rate contribution number PRN satisfies the formula (2), The resin constituting the polishing pad is any one of PSU (polysulfone) resin, PPSU (polyphenylsulfone) resin, PEG#400 acrylic resin (acrylic resin obtained by UV-curing an acrylate monomer in which an acrylic group is bonded to both ends of a polyethylene glycol having an average molecular weight of 400), PC (polycarbonate) resin, and PVDF 80% + HFP 20% (copolymer resin of polyvinylidene fluoride 80% and propylene hexafluoride 20%).
1. A method for polishing a semiconductor wafer, comprising: PRN=-5738M H +849.6M C +1766M O -40.7M N -394.9M S +219.4M F ・・・ (1) 268.4≦PRN≦1516.3 … (2)
6. The polishing rate contribution number PRN of the polishing pad satisfies the formula (3).
6. The method for polishing a semiconductor wafer according to claim 5. 268.4≦PRN≦959.3 … (3)
7. The polishing liquid contains an aqueous solution of potassium permanganate as the aqueous solution of the strong oxidizing agent.
6. The method for polishing a semiconductor wafer according to claim 5.
8. The polishing pad is made of any one of a resin having no abrasive grains and no independent or interconnected pores, a resin having independent and / or interconnected pores, and a resin containing at least one of silica abrasive grains, alumina abrasive grains, zirconia abrasive grains, manganese oxide abrasive grains, and ceria abrasive grains as abrasive grains within the independent and / or interconnected pores.
6. The method for polishing a semiconductor wafer according to claim 5.
Citation Information
Patent Citations
Polishing tool and manufacturing method therefor
JP2003011066A
Method for polishing semiconductor wafer
JP2013214784A
Polishing method for semiconductor wafer
JP2021057368A
POLISHING METHOD AND POLISHING LIQUID FOR InP SEMICONDUCTOR MATERIAL
JP2021061306A
CMP polishing device
JP2022094554A